(untitled) - Galin, Daniel (Harlow, England, 2004)
This book emphasizes the application aspects of software quality assurance (SQA) systems by discussing how to overcome the difficulties in the implementation and operation of them. State-of-the-art topics for software testing and managing SQA activities, such as computerized tools, are incorporated into the text and emphasized through the author's use of real world examples. Software developers who want to enhance their knowledge of SQA systems.
Keywords: Computer software,Phần mềm máy tính; Quality control,Kiểm soát chất lượng